Transformation Chains, Associative Areas, and a Principle of Form for Anton Webern's Twelve-tone Music. (12th June 2019) - Moseley, Brian
Abstract: Much of Webern's twelve-tone music relies on conventional formal types to structure extended composition and long-range compositional strategy. This article describes how these forms were absorbed into his personal twelve-tone style through an exploration of three entwined techniques. His techniques of serial row chaining and associative organization create a deep musical hierarchy that is frequently navigated by a formal principle of large-scale complementation. The analyses appearing here are drawn from across Webern's twelve-tone period and are elucidated through spatial representations that describe compositional potential and musical realization. In addition to providing a means for analytical interpretation, the analyses reveal how Webern's fusion of form and twelve-tone technique resemble characteristics of the tonal system while amplifying basic axioms of serial composition.